2015
DOI: 10.1038/jcbfm.2014.258
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of MR Detectable Cortical Microinfarcts: A Classification Study with 7-Tesla Postmortem MRI and Histopathology

Abstract: Cerebral microinfarcts (CMIs) are common neuropathologic findings in aging and dementia. We explored the spectrum of cortical CMIs that can be visualized with 7T magnetic resonance imaging (MRI). Thirty-three coronal brain slices of 11 individuals with neuropathologically confirmed dementia were subjected to a high-resolution postmortem 7T MRI protocol. First, we identified all visible small (⩽5 mm) intracortical and juxtacortical lesions on postmortem MRI. Lesions were classified as CMI or nonCMI based on his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 30 publications
1
77
0
1
Order By: Relevance
“…Recent radiologic-pathologic studies have shown that microinfarcts of approximately 1 to 2 mm can be detected on 3-and 7-Tesla in vivo MRI scans ( Figure 1C). 67,68 However, microinfarcts can be as small as 100 microns, 54,63 thus a large proportion of these lesions remain invisible on brain imaging. 10 The rapid development of imaging techniques and optimization of T1-and T2*-weighted MRI sequences, both on 7 Tesla and on lower field strength MRI, makes it likely that we will be able to quantify smaller lesions in vivo in the near future.…”
Section: Microinfarctsmentioning
confidence: 99%
“…Recent radiologic-pathologic studies have shown that microinfarcts of approximately 1 to 2 mm can be detected on 3-and 7-Tesla in vivo MRI scans ( Figure 1C). 67,68 However, microinfarcts can be as small as 100 microns, 54,63 thus a large proportion of these lesions remain invisible on brain imaging. 10 The rapid development of imaging techniques and optimization of T1-and T2*-weighted MRI sequences, both on 7 Tesla and on lower field strength MRI, makes it likely that we will be able to quantify smaller lesions in vivo in the near future.…”
Section: Microinfarctsmentioning
confidence: 99%
“…These focal elongated lesions were hyperintense on 7T FLAIR (0.8 mm isotropic voxels), restricted to the cortex and seemed to extend from the cortical surface, hyperintense on T2 (0.7 mm isotropic voxels), and hypointense on T1 (1.0 mm isotropic voxels). It was confirmed that these lesions were cortical CMIs using an MR-guided histopathology approach in post-mortem human brain tissue 6,7 .…”
Section: Introductionmentioning
confidence: 65%
“…2. Assess cortical CMIs on the in vivo 7T MR images as detailed in the steps below, using the following 7T rating criteria for CMIs: cortical CMIs are hyperintense on FLAIR (with or without a hypointense center), hyperintense on T2, hypointense on T1, detectable on at least two views of the brain (e.g., sagittal and transversal), restricted to the cortex, distinct from perivascular spaces, with a greatest dimension ≤4 mm 6,7 . 3.…”
Section: Assessing Cortical Microinfarcts On In Vivo 7t Mrimentioning
confidence: 99%
“…A recent post-mortem study of confirmed dementia cases found WMH pathology was consistent with microinfarcts, except for in juxtacortical lesion, which were enlarged perivascular spaces (34). Other research suggests ischemic, rather than small vessel disease, has a prominent role in WMH pathophysiology (35).…”
Section: The Pathophysiology and Development Of Wmhsmentioning
confidence: 99%